Parameters of the ”˜Honor and Dignity’ Element in the Criminal Act of Sexual Violence - Marpaung, Jessica Vincentia; Triwinata, Jiu Jiu (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Law Number 12 Year 2022 concerning the Criminal Acts of Sexual Violence (UU Tindak Pidana Kekerasan Seksual/“Sexual Violence Law”) seems to provide a moment of calm amidst the high number of sexual violence cases that occur in Indonesia, but does Sexual Violence Law really adhere to the principles of utility, justice, and especially, certainty? One of the focuses of the Authors’ research is the element of ”˜honour and dignity’ (harkat dan martabat) contained in Articles 5 and 6 of Law Number 12 Year 2022 on Criminal Acts of Sexual Violence regarding sexual harassment that is carried out physically or non-physically. Honor and dignity are abstract concepts and cannot be measured because they are parts of the nature of human beings as God’s creation. The assessment of what ”˜honor and dignity’ is and its worth is highly relative and can be very different when viewed from not only the perpetrator and victim’s perspectives. Therefore, this article seeks to assess whether there is a more definitive set of elements to define sexual violence. This article uses normative research study to investigate into and apply the concept of a “Reasonable Person”, the application of which can also be useful in the ambit of criminology, especially victimology, especially to address sexual violence cases where the victim’s position should be considered (pro-victim approach).